2022
DOI: 10.1111/odi.14323
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral lichen planus in patients with diabetes mellitus: A cross‐sectional study

Abstract: ObjectivesOral lichen planus, a chronic inflammatory immune disease, occurs in the oral mucosa. We aimed to assess the prevalence and possible influencing factors of oral lichen planus in patients with diabetes mellitus.Subjects and MethodsThis cross‐sectional study involved 525 patients with diabetes mellitus and 525 controls. We collected information on blood glucose level, duration of diabetes, diabetic complications, treatment methods, other systemic diseases and medication history.ResultsOral lichen planu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Regarding the clinical type, the majority of OLP patients with DM manifested with the white "reticular" type (8 patients (66.7%)), while the atrophic type was observed in only 4 patients (33.3%). This finding was in line with previous studies, where a higher prevalence of the reticular type was reported among OLP patients with DM [17,18].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding the clinical type, the majority of OLP patients with DM manifested with the white "reticular" type (8 patients (66.7%)), while the atrophic type was observed in only 4 patients (33.3%). This finding was in line with previous studies, where a higher prevalence of the reticular type was reported among OLP patients with DM [17,18].…”
Section: Discussionsupporting
confidence: 93%
“…The association between DM and OLP is still controversial in the literature [17]. In our study, a total of twelve OLP patients were found to have DM.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, patients with DM and/or TD should undergo periodic oral mucosa examinations to rule out OLP. 10 , 11 , 12 Cross-referral of OLP patients seen in oral medicine to endocrine department for investigation and management of comorbidities. The impact that these proposals could have on health outcomes both in one group and another of patients should be analyzed in new specific studies designed for it, which could serve as recommendations to improve and standardize future research.…”
Section: Discussionmentioning
confidence: 99%
“…The most common comorbidities of LP are hepatitis C virus infection (HCV) and thyroid disease [ 2 , 12 ]. Recently, metabolic syndrome (MS), type 2 diabetes (T2D) and dyslipidemia have also been reported to be associated with LP [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Additionally, LP patients have increased risk for cardiovascular diseases [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%